Tiras e gramática do design visual: a produção de sentidos no gênero multimodal - Cunha, Andreia Honório da (2017)
This research has for theme the multimodal textual and discursive organization of strip comics genre dealing with sense complementary among words and image. Its situated in “Text and discourse in oral and written modalities” of the Program of Postgraduated Studies in Portuguese Language by PUC – SP. Sociossemiotic area embases the research and has as its primary theoretical basis the Grammar of Visual Design, written by Kress and van Leeuwen, (1996). It privileges the study of the multimodal genre and has as its theme the textual and discursive organization of comics forms expressed in strips. The general objective of this research is to contribute to the improvement of the multimodal studies in brazilian strips as well as the pertinence of the social problems exposed in these texts. To accomplish this goal, the narrative construction of the strips must be verified, including the graphical and verbal-descriptive examination of the semiotic landscape as well as the graphical and verbal-descriptive analysis of the metafunctions: representational, interactional and compositional. By means of these actions the value of the information subdivided and positioned in given and new, considering the opposition of the semioses expressed in the right and left laterality and ideal and real is considered, considering the opposition of the semioses expressed above and below the frame. This approach includes the saliencies and subjectivities related to the choices of the producer in the exposition of the frameworks. By means of the above, we examine the permissive transgression and rupture of the performance of the sarcastic and the jocose, which, finally, refer to both the laughter and the critic of the problematic exposed and in the proposal to be discussed and reflected. In this context, the investigation is methodologically exposing the theoretical frameworks and applying them to the practice favoring the identification, the understanding and the sensitization to the notoriety of the amplification in the production of meanings established in this relation of complementarity of the communicative semiotic resources